"A world to win": China, the Afro-Asian Writers' Bureau, and the Reinvention of World Literature. Issue 2 (3rd April 2019) - Vanhove, Pieter
ABSTRACT: This article analyzes Chinese contributions to the Afro-Asian Writers' Bureau's efforts to reinvent World Literature from an anti-imperialist and anti-capitalist perspective. The Afro-Asian Writers' Bureau was founded as a counter-narrative to Eurocentric conceptions of World Literature and universal culture. The AAWB's vision was inspired by a Marxian understanding of worldliness. Relying on Chinese archival materials, this article shows how Chinese representatives to the AAWB, including Zhou Yang and Mao Dun, shifted from an explicitly Soviet, socialist-realist model for World Literature inspired by Maxim Gorky to a progressively independent, nationalist course in the wake of the Sino-Soviet split. The story of the AAWB is one of competing universal visions. The Chinese contributions to the AAWB are also reflected in China's current expanding cultural influence and soft power in the Global South.